The Efforts of Handling Transportation Problems in DKI Jakarta Through Sustainable Transportation Policy - Khafian, Nidaan (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
Transportation problems in Jakarta are very complex. There are three common problems occuring, such as uncontroled numbers of private vehicles, poor and unreliable condition of public transportations, and indisciplined behavior of road users. This study discusses the efforts to handle transportation problems in Jakarta using the concept of sustainable transportation. Using qualitative research method, the results of the study showed that there are some efforts that had to been done in short-term, medium-term and long-term in accordance with the concept of sustainable transportation. In short-term, the efforts are the implementation of direct services and the organizing of public transport. In medium-term, the efforts are the construction of the MRT and LRT, and also the arrangement of pedestrian lanes. Meanwhile, in long term, the government must integrate the spatial policies with transport policy and establish special authority on Jabodetabek transportation. The results also suggest that there are urgencies to have a shift in the paradigm and mindset of both central and local governments, from transportation policies that favor for private vehicles into policies that favor for public transport, as well as the courage and commitment of the provincial government of DKI Jakarta to implement the efforts gradually and sustainably.